Stakeholders Engagement and Performance of Sustainable Information Quality - Oliveira, Selma; Júlio, Lais; Oliveira, Richard; Midori, Fernanda (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2023)
Integrated reporting (IR) is considered an innovative and effective reporting tool that includes both financial and non-financial information. Recently, there has been a greater emphasis on IR both from the point of view of the relevance of sustainable information. This study relates stakeholder engagement and performance of sustainable information quality in an emerging economy. There are few scientific contributions that evidence this relationship. This research defends this relationship in the light of the information produced by the IR. Using a judgment matrix, a survey was applied to professionals from multinational sustainable manufacturing companies in Brazil. The findings indicate that the engagement of stakeholders has a positive and significant effect on the performance of the quality of economic, social and environmental information. To the best of our knowledge, this is the first study that investigates the relationship between stakeholder engagement and performance of sustainable information quality. This study has implications.